2020
DOI: 10.1016/j.ijnurstu.2020.103725
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the caregiver during COVID-19 outbreak: Does inclusive leadership improve psychological safety and curb psychological distress? A cross-sectional study

Abstract: Background Public health emergencies and epidemics shatter the assumptions of the world as a safe place. Healthcare workers are at the forefront of such pressures resulting from a persistent threat to their safety and well being. It is therefore important to study such mechanisms that can influence and predict the psychological distress of nurses Objectives While there is an increasing number of studies on positive outcomes of leadership styles, their influence on curbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 78 publications
0
132
1
6
Order By: Relevance
“…Working under respectful superiors was further described as a positive factor during the pandemic by interviewees. According to Zhao et al [ 84 ], inclusive leadership could be a mediating factor regarding distress and important for nurses in hospitals during the COVID-19 pandemic. Feeling more appreciated for their work at their workplace and/or by fellow people was another relevant job resource of our interviewees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working under respectful superiors was further described as a positive factor during the pandemic by interviewees. According to Zhao et al [ 84 ], inclusive leadership could be a mediating factor regarding distress and important for nurses in hospitals during the COVID-19 pandemic. Feeling more appreciated for their work at their workplace and/or by fellow people was another relevant job resource of our interviewees.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD was also found among outpatient caregivers [ 68 ], as well as feeling threatened [ 45 ] or even having suicidal thoughts [ 40 , 41 ]. A positive strain reaction—decrease of stress perception due to work resources—was shown in one study on nursing staff [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this critical time, the role of leadership cannot be ignored (Billings et al, 2020;Sant'Ana et al, 2020;Zhao et al, 2020a). While studies have shown that transformational leadership, inclusive leadership and servant leadership seems to be a suitable leadership style for managing employees working in education sector during this pandemic, there is no evidence on the effectiveness of these leadership styles in hospitals settings and occupational safety offered by these leadership styles (Azizaha et al, 2020;Fournier et al, 2020;Zhao et al, 2020b;Antonopoulou et al, 2021;Piorun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Workers experience satisfaction in doing work well and are supported or restrained by their work environment. New evidence from research on human factors and the value of psychological safety for workers—feeling free from bullying and incivility—is clarifying the need to feel supported in speaking up about unsafe care [ 23 ]. New studies examine the impact of human factors on how workers complete their work, including fatigue, interruptions, distractions, broken processes, unreliable equipment, and other human workplace interfaces [ 24 ].…”
Section: Learning Organizations: a Systems Approach To Safety And Quamentioning
confidence: 99%